KEDUDUKAN JANDA DALAM HUKUM WARIS ADAT, PERDATA, DAN ISLAM: KAJIAN INTEGRATIF - Halim, Abd (UIN Sunan Kalijaga Yogyakarta, 2017)
The inheritance law prevailing in indonesia is pluralistic since it consists of customary inheritance law (Adat), civil inheritance law (KUH Perdata), and Islamic inheritance law. This is inseparable from the politic of law performed by Dutch-Indische Government about population classsification in article 131 and 163 Indische Staatsregeling (S.1855-2). The influence of this policy is visible even now because there are some differences in their principles and norms. The difference in principle such as application of “legitieme portie” principle that is exist in civil inheritance law is unheard in Adat law, while the Islamic law has ijbrari principle. Another differences lay in the inheritance elements. In Adat, element of kinship between someone and his/her heir is very important. Civil inheritance law, in other hand, has two ways to determine how the heritage can be passed down, first is arranged in constitution, and second is mentioned in testament letter. Islamic law also has two ways to determine the inheritance right that consist of kinship elements (nasabiyah) and inheritance relations that built by marriage, etc (sababiyah). The consequence of this differences affecting widow’s position as a heir because of its acknowledgement in civil and Islamic law, while Adat doesn’t recognize it. This paper is trying to find a way to integrate this matter with law harmonisation theory and other relevant theories.